1988
DOI: 10.1159/000146510
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of the Myelin Sheath to Axonal Atrophy in the Rat Spinal Root by the Formation of Infolded Myelin Loops

Abstract: Atrophy of the L4 dorsal and ventral spinal roots was experimentally induced by unilateral sciatic neurectomy in groups of young (2 and 4 months) and older (12 months) albino rats. During the 4 months following neurectomy, the occurrence of infolded myelin loops (IMLs) was quantitatively examined in transverse sections prepared using perfusion fixation with glutaraldehyde and embedding in epoxy resin. The number of IMLs was higher on the operated side and increased with the time of survival and the age of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
7
1
1
Order By: Relevance
“…MF with irregular shapes could be indicative of the first steps of axonal atrophy. In most cases, large irregular fibres show abnormalities in the myelin sheath such as wide incisures, separation of lamellae and myelin loops, all of which are common features of axonal atrophy (Krinke et al 1988). In addition, changes in the density of nerve fibres, in the amount of collagen and variations in myelin thickness can influence the maintenance of a circular shape of MF in older animals.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…MF with irregular shapes could be indicative of the first steps of axonal atrophy. In most cases, large irregular fibres show abnormalities in the myelin sheath such as wide incisures, separation of lamellae and myelin loops, all of which are common features of axonal atrophy (Krinke et al 1988). In addition, changes in the density of nerve fibres, in the amount of collagen and variations in myelin thickness can influence the maintenance of a circular shape of MF in older animals.…”
Section: mentioning
confidence: 99%
“…Myelin loops have been described during the first stages of development and interpreted as steps in the process of myelin recycling (Jacobs & Love, 1985). However, the increased frequency of IML with ageing has been related to an early response of large calibre myelin sheaths to axonal atrophy (Krinke et al 1988). According to our observations, the increased number of OML in aged nerves could indicate a disruption in the maintenance of the compact structure of myelin sheaths, as well as alterations in the rate of removal of myelin products.…”
Section: mentioning
confidence: 99%
“…Northern analysis showed that neurofilament mRNA levels remained relatively constant between 3 and 12 months of age, but decreased by approximately 60% at 23 months of age in the rat ( Parhad et al, 1995 ) . In most cases, large irregular fibers show abnormalities in the myelin sheath such as wide incisures, separation of lamellae and myelin loops ( Knox et al, 1989 ) , all of which are common features of axonal atrophy ( Krinke et al, 1988 ) . In addition, segmental demyelination ( Sharma et al, 1980 ; Adinolfi et al, 1991 ) , swollen demyelinated and remyelinated axons, some encircled by supernumerary cellular processes and collagen pockets, and denervated Schwann cell columns ( Grover‐Johnson and Spencer, 1981 ) are other peripheral nerve abnormalities observed in aging animals.…”
Section: Introductionmentioning
confidence: 99%
“…The morphometry evaluation of myelinated nerve fibres with abnormal myelin sheaths was further defined as myelinated nerve fibres with (1) infolded myelin loop, (2) outfolded myelin loop, and (3) separation of lamellae or wide incisures according to previous studies . Semi‐thin sections were examined at an original magnification of ×40.…”
Section: Methodsmentioning
confidence: 99%